Kontekstualitas Ayat Tentang an-Nafs dalam al-Qur’an (Analisis Kajian Psikologi Pendidikan Islam) - Sejati, Sugeng; Azizi, Arief; Hermanto, Doki; Nyilih, Lumenta Rinaldy Dalalna; Yunita, Nurma; Warsah, Idi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Psychology is a science that studies the human soul, but errors often occur in understanding a person's initial condition, resulting in misunderstandings in studying and healing a person's mental problems, which results in not healing being obtained but the opposite. In this article, we discuss what psychological studies are in the perspective of the Koran by analyzing verses about the nafs. It was found that in humans there are drives that make them carry out certain actions and it is these drives that must be understood by a psychologist.